Territorialisation et sens politique des incitations financières à la récupération et à l’utilisation de l’eau de pluie - José-Frédéric Deroubaix; Bernard de Gouvello; Cédric Moreau de Bellaing (Territoire en Mouvement)
This paper focuses on the process of inscription on the national and local political agendas of the issue of rainwater reuse. This process led to the implementation of different types of financial incentives. The 2006 Water Act provisions dedicated to rainwater reuse and 32 different types of local incentives are here presented. The analysis is completed through a deep analysis of eight cases, typical of the various types of financial incentives and success or failure recorded. This analysis enlighten the existing relations in between this types of policy instruments and the political territories involved in their implementation and, on the contrary, the lack of consideration for the hydrological and social characteristics of the concerned areas.Even though these incentives are very heterogeneous, they present a common characteristic: they all seem to be designed without concern for their efficiency. The purpose is more to encourage the awareness of an ecological value of the water rather than to maximise the number of subsidised people or the volume of reused water. In the paper we test the hypothesis of this policy of financial incentives being driven by a will to build a symbolic value of rainwater. The statement of this symbolic value is a good way to free from controversies regarding the economic and social benefits of the water reuse. Rain water is per se good and therefore should be used. Use drinkable water, at least for outdoor purposes, is to waste and to spoil it. Therefore the inclination of local technicians and elected representatives for this type of policy instruments is meaningful.Financial incentives are good tools for encouraging inhabitants willing to conform to the moral value of rainwater. As a significant contribution is required from the ones benefiting the subsidy, the incentive operates as a reward for the people willing not to spoil anymore the “providential” rainwater. Even though these local policies are territorialised, responding to a will of local stakeholders to mobilise the inhabitants, they do not take into account the territorial and environmental context of their implementation.